Good corporate governance on performance: The moderating role of covid-19 - Susanti, Tri Yuli Tiastuti; Raharja, Surya (Jurnal Fokus Manajemen Bisnis, 2024)
This study highlights the importance of good corporate governance in company performance, especially during the Corona Virus Disaster 2019. This study examines the impact of various factors on firm performance, with an emphasis on corporate structure and practices. The variables under investigation include board size, board independence, board gender diversity, board meetings, board financial qualifications, audit committee size, and audit committee meetings. This study analyzed 137 manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021, which were selected using a purposive sampling method. The analysis used panel data regression and descriptive statistics using STATA tools. The analysis used panel data regression and descriptive statistics using STATA tools. The results showed that board size, board independence, and audit committee meetings improved company performance during crises. However, the presence of women on the board, frequency of board meetings, and financial education of board members can negatively impact performance.